Analisis Penyetelan Relai Arus Lebih Dan Gangguan Tanah Sebagai Proteksi Pada Jtm 20 Kv - Siregar, M. Ikhsan; Hasyim Rosma, Iswadi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
This article uses observations aimed at analyzing the settings for overcurrent relays and ground disturbance in the 60 MVA transformer. With the data obtained such as CB data, transformers, overcurrent relay specifications, ground fault relays, load data, and channel data used to obtain 3 phase short circuit current, 2 phase and one ground phase on the incoming and feeder side using ETAP simulation 12.6.0. For overcurrent relays that are on the Incoming side using the calculation of TMS = 0.19s while on the TMS field = 0.24s. The ground fault relay on the incoming side uses the calculation of TMS = 0.2s while those in the field are 0.24s. The overcurrent relay in the folding feeder uses the TMS = 01s calculation while in the TMS field = 0.12s. So the overcurrent relay and ground disturbance relays on the Incoming side of the field must be rearranged.Keywords: protection, overcurrent relay, ground fault relay, ETAP 12.6.0